Analisis Kinerja Keuangan Perusahaan Makanan Cepat Saji dengan Pendekatan Rasio Likuiditas, Solvabilitas, dan Profitabilitas - Ibnu Mas’ud; Nur Ainiyah; Nurdiana Fitri Isnaini (CV. Kalimasada Group, 2025)
This This study aims to analyze the financial performance of PT Fast Food Indonesia Tbk during the 2021–2024 period using liquidity, solvency, and profitability ratio approaches. The research method employed is descriptive quantitative, with financial ratio analysis covering the Current Ratio (CR), Quick Ratio (QR), Cash Ratio, Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Interest Coverage Ratio (IC), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The conclusion reveals that the company’s liquidity decreased, solvency remained at a high leverage level, and profitability improved towards the end of the period. These results indicate that although the company has improved operational efficiency and asset management, financial risk remains high due to reliance on debt-based financing. The study recommends strategies to strengthen liquidity, control leverage, maintain sustainable profitability, and implement comprehensive financial risk management to ensure long-term financial stability.